2017
DOI: 10.1190/geo2016-0076.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost time-lapse seismic with distributed compressive sensing — Part 1: Exploiting common information among the vintages

Abstract: Time-lapse seismic is a powerful technology for monitoring a variety of subsurface changes due to reservoir fluid flow. However, the practice can be technically challenging when one seeks to acquire colocated time-lapse surveys with high degrees of replicability among the shot locations. We have determined that under “ideal” circumstances, in which we ignore errors related to taking measurements off the grid, high-quality prestack data can be obtained from randomized subsampled measurements that are observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Oghenekohwo et al . (2015, 2017) and Wason et al . (2017) designed a cost‐efficient non‐repeated time‐lapse acquisition and then proposed to use a joint recovery scheme based on the curvelet transform to recover the four‐dimensional vintages.…”
Section: Introductionmentioning
confidence: 94%
“…Oghenekohwo et al . (2015, 2017) and Wason et al . (2017) designed a cost‐efficient non‐repeated time‐lapse acquisition and then proposed to use a joint recovery scheme based on the curvelet transform to recover the four‐dimensional vintages.…”
Section: Introductionmentioning
confidence: 94%
“…Oghenekohwo et al . (), Wason, Oghenekohwo and Herrmann (), Qu and Verschuur (, ) and Carpentier and Boullenger () demonstrated that if time‐lapse acquisitions are done with designed non‐repeatable sparse acquisition, a better time‐lapse response will be provided compared to the sparse repeated monitoring acquisition. Some researchers have already done investigations on the non‐repeatability issue.…”
Section: Introductionmentioning
confidence: 99%